A Flower‐like Bismuth Oxide as an Efficient, Durable and Selective Electrocatalyst for Artificial N2 Fixation in Ambient Condition. Issue 7 (28th February 2019) - Chang, Bing; Liu, Qin; Chen, Ninghua; Yang, Yingchun
Abstract: Ammonia is a basic industrial chemical, which is widely used in industry and agriculture. Traditional Haber–Bosch N2 fixation process is not environmentally friendly, which not only excessively consumes energy, but releases enormous amount of greenhouse gas. Electrochemical N2 reduction is an ideal alternative to N2 fixation, but it requires effective electrocatalyst for N2 reduction reaction (NRR). Herein, we develop a flower‐like β‐Bi2 O3 catalyst for artificial N2 fixation with outstanding NRR performance and selectivity in ambient condition. This β‐Bi2 O3 nanoflower shows an excellent NH3 yield of 19.92 μg h −1 mg −1 cat. and Faradaic Efficiency of 4.3 % at −0.8 V in 0.1 M Na2 SO4 solution, better than most reported NRR electrocatalysts. This electrocatalyst also exhibits superb electrochemical stability and durability. Abstract : Catalysis in bloom : A flower‐like beta bismuth oxide shows an excellent NH3 yield of 19.92 μg h −1 mg −1 cat. and Faradaic Efficiency of 4.3 % at −0.8 V with good selectivity in 0.1 M Na2 SO4 solution.A flower‐like bismuth oxide as an efficient, durable and selective electrocatalyst for artificial N2 fixation in ambient condition from @Chengdu_China